How Elementary School Teachers Integrate Technology in Social Studies Learning during the COVID-19 Pandemic? - Herwin, Herwin; Dahalan, Shakila Che (Jurnal Pendidikan Progresif, 2022)
How Elementary School Teachers Integrate Technology in Social Studies Learning during the COVID-19 Pandemic? Objectives: This study aims to find out how elementary school teachers integrate technology in social studies learning during the COVID-19 pandemic. Methods: This study uses a phenomenological approach, then interviews and documentations are used to collect the data. There are 6 elementary school teachers who participate in this study from Yogyakarta, East Java and Bangka Belitung. Data analysis: The data required are analyzed using qualitative data analysis techniques. Findings: This study finds out that teachers use technology as the main element in distance learning; synchronous learning using zoom; asynchronous learning using WhatsApp, google form, google classroom, Quizizz, YouTube; and the combination of both; obstacles that are often faced include technical constraints, economic capacity problems, and human error. Conclusion: There are still many obstacles faced by teachers and students regarding the use of technology in social studies learning.Keywords: elementary school teachers, integrate technology, social studies, COVID-19 pandemicDOI: http://dx.doi.org/10.23960/jpp.v12.i1.202201